2018
DOI: 10.4236/fns.2018.96054
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fatty Acid Composition in Men over 50 in the USA and Japan

Abstract: Background: Coronary heart disease (CHD) rates differ markedly between the US and Japan. Fatty acid profiles have been linked to risk for CHD. Few studies have compared the plasma fatty acid composition, including trans fatty acids, in Japanese and US subjects. Methods: Fasting blood samples were taken from healthy older (>age 50) American (n = 76) and Japanese (n = 44) men, and plasma levels of 23 fatty acids were analyzed by gas chromatography and expressed as a percent of total fatty acids. Results: As expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…We found that IP-trans fatty acids were lower in Japan vs the US [8]. The reported intake of IP-TFA is 0% in Japan, again supporting the observed differences in biomarker levels.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found that IP-trans fatty acids were lower in Japan vs the US [8]. The reported intake of IP-TFA is 0% in Japan, again supporting the observed differences in biomarker levels.…”
Section: Discussionsupporting
confidence: 80%
“…Table 3 shows plasma levels of fatty acids including ω fatty acids and trans fatty acids. Compared with old men in USA, plasma levels of DHA and EPA were higher in Japanese men and plasma levels of elaidic and linoelaidic acids were higher in Old mane in USA [8]. Table 4 shows that there were no correlations between foods intakes and plasma levels of trans fatty acids and that only preference drinks such as tea and coffee had significant correlations with plasma levels of palmitoelaidic acid and linoelaidic acid.…”
Section: Other Plasma Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…In recent studies comparing TFA levels between US and Japan, both we and others have observed much lower levels in Japan, consistent with lower CHD rates [18.19]. Our recent study with Japanese and American older men (> age 50) showed markedly lower levels of elaidic and linoelaidic acids (IP-TFA) and significantly higher levels of palmitelaidic acids (R-TFA), compared with American men [18]. The Hawaii-Los Angeles-Hiroshima Study reported that serum elaidic acid concentrations in the native Japanese living in Hiroshima were significantly lower than those in the Japanese-Americans living in Los Angeles [19].…”
Section: Tablesupporting
confidence: 79%
“…Dihomo-g-linolenic acid is converted to arachidonic acid. We have indicated that plasma levels of AA and dihomo-g-linolenic acid (DHGL) were lower in Japanese than American [23]. Since oils and meat contain AA (Figure 3), we thought that American people intake more meat and oils than Japanese resulting in increased plasma levels of AA and dihomo-g-linolenic acid.…”
Section: Discussionmentioning
confidence: 99%